(untitled) (Journal of Parents and Teachers, 2013)
The author of this article talks about the concept of “areas of learning and assessment”. The main objective is to make a reference of the development of the process of teaching and learning in the everyday life in the classroom, place in which the students learn concepts. In this articles is also highlighted the characteristics, elements and phases of the process of assessment. Every single theory is complete with examples.